SPORTS PROGRAM TO PROMOTE POSITIVE YOUTH DEVELOPMENT (PYD) (Study literature review) - Sari, Prilina Mayang; Ma’mun, Amung; Firmansyah, Helmy (Universitas Pendidikan Indonesia, 2024)
Many things can influence the growth and development of teenagers, in this case young people, one of which is in the world of sports. Among them are sports programs that can make changes to the characteristics of youth development for the better, both physically and mentally for themselves or even their social environment. In this effort, the world of sports can be one way to make youth development in a more positive direction. The aim of the research here is focused on comparing the results of journals and articles that the author obtained with the keywords sports program physical education literature review, systematic literature review and positive youth development. This journal search was based on search results on Google Scholar and Taylor Francis, researchers found 5,657 journals that matched these keywords. A total of 418 journals were found to match these keywords exactly, then screening was carried out and 197 journals were found to be excluded because they had the same title and no full text articles were available and 221 journals were produced for abstract screening and the results obtained were 76 journals. 44 journals that were duplicates and did not meet the inclusion criteria were excluded so that 20 full text journals were reviewed. Because this research could not be carried out in the field during the Covid-19 pandemic, a narrative literature review method was carried out using data from 5657 journals that were initially found. Based on the results of the research analysis and the implications of the analysis, there is an influence of sports programs to promote positive youth development in the world of sports. So it is hoped that in the future we will be able to explore other factors that can influence or encourage positive development in young people. and be able to explain more fully the benefits of positive youth development programs.